Increased Crop Productivity Through Efficient Management of Soil and Water Resources on Watershed Basis at Tejpura - Hazra, C.R. (Journal of Soil and Water Conservation, 2022)
An area of 775.7 ha was treated with soil and water conservation measures on watershed basis at the Tejpura village of Jhansi district. The area experiences a rainfall of 940 mm with 93 per cent during rainy season. The soils are mostly silty clay Imams and loamy sands. Four check darns have been constructed across a seasonal nallah of 6.5 km in length at a vertical interval of 3.5 m each with total water impounding capacity of 12 ha m for supplemental irrigation. The initial irrigated area was aonly.1.8 per cent Whkh subsequently rose to 78 per cent. The dug out wells were also increased from 5 to 35 with irrigation potentiality from 1-2 hours to 8 to 10 hours in a day with rise in water table from 3 to 7 M. Sorghum intercropping, with pigeonpeablack gramgreen is most productive cropping system during kharif ( 2.2 Oa) and wheat recorded highest production ( 3.65 Oa). The initial annual land productivity of 0.60 t/ ha increased to a record 5.31 t I ha and the average crop yields recorded a four fold increase ( 0.73 t ’ha to 2.95 Wm). The total annual production increased to 7722 t from 2238 t and the B..0 ratio was at 3.71. Earner’s participation in the programme was excellent The interaction and colloboration between the Research Group and the Development Department was exemplary.